PENGARUH PENGALAMAN, INDEPENDENSI, SKEPTISISMER PROFESIONAL AUDITOR PADA PENDETEKSIAN KECURANGAN - Yessy Angelita Siantari; Suzy Novianti (JRAK: Journal of Accounting Research and Computerized Accounting, 2024)
This research was conducted with the aim of knowing and testing the influence of experience, independence and professional skepticism of auditors on fraud detection. This research was conducted at a Public Accounting Firm in Central Java. The sample used was 37 auditors. The data in this study was collected using a questionnaire method. The data analysis technique used is Multiple Linear Regression Analysis. The results of hypothesis testing show that experience has a positive effect on fraud detection, independence has a positive effect on fraud detection, and Auditor Professional Skepticism has a positive effect on fraud detection. Based on the results of the multiple linear regression test, it was found that the independence variable was the most dominant variable in detecting fraud.